Steganography with pixel-value differencing and modulus function based on PSO - Li, Zhaotong; He, Ying (Journal of information security and applications, 2018)
An effective steganographic scheme is proposed that combines pixel-value differencing, modulus function, and particle swarm optimization on the basis of previous research. In this paper, the difference between neighboring pixels in the carrier image is used. Pixel-value differencing and the modulus function are used to embed and extract secret information. Also, particle swarm optimization is used to select the ideal pixel gray values among numerous modulus function solutions to improve the quality of the stego-image. In the final experimental results, the proposed method had better embedded capacity and steganographic quality than schemes proposed by previous researchers.